An application of knowledge management to document guided schools necessary information - Foroogh Bigdeli; Yadoola Mehr Ali Zadeh (Management Science Letters)
This paper presents an empirical investigation on how to document some experiments on special and governmental guidance schools managers of Abadan province in Iran. Statistical society of this research includes all education managers and teachers in governmental and nongovernmental guidance schools of Abadan province located in southern part of Iran. The study selects 222 teachers and managers, randomly, and using some questionnaires, we try to find important items to document. The questionnaire covers 6 main groups including students, teachers, school manager, connection with parents, connection with society, education planning. The study finds out whether there was any difference between teachers’ educational background and six groups of people. However, the investigation does not find any difference between teachers’ educational background and six groups of studies.